A SPECIAL AUTONOMY: A COMPARATIVE STUDY OF THE PAPUA AND ACEH CONFLICT IN THE PERSPECTIVE OF SPECIAL AUTONOMY - Sufajar, Rahmat; Siti Sadiyatunnimah; Muqaddim; Cleorissa Cheguevara (Journal of Social Political Sciences, 2025)
The Indonesian government created the Special Autonomy Policy in 2001 to prevent conflict and accelerate development in regions with distinct historical, social, and political characteristics. However, after more than two decades of implementation, the establishment of Special Autonomy in Aceh and Papua has produced mixed results, particularly in terms of political stability, governance, and national integration. This study begins with the topic of why Special Autonomy has strengthened national integration in Aceh but not in Papua? The goal of this study is to assess the effectiveness of Special Autonomy in promoting national integration and to determine the factors that influence the policy's success or failure based on the local environment of each region. The research technique employs a comparative qualitative approach that includes policy document analysis, literature reviews, and the tracking of empirical data from development reports and political dynamics in Aceh and Papua. The study's findings indicate that the existence of the Helsinki peace accord, political representation channels through local parties, and a somewhat more restricted level of responsibility for Special Autonomy monies all contribute to the Aceh Special Autonomy's success. However, in Papua, there are still development inequities, a lack of avenues for political representation of indigenous peoples, and low trust in the state, resulting in a suboptimal national integration process. This study is unique in that it evaluates Special Autonomy as a tool for reconciliation and trust-building, as well as economic policy and political decentralisation